2021
DOI: 10.21511/bbs.16(1).2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee attributes, board attributes and market performance of listed deposit money banks in Nigeria

Abstract: This paper aims to discover the association between various audit committee and board attributes and the market performance of listed deposit money banks in Nigeria. The study intends to determine the influence of audit committee size, gender diversity, expertise, board size and board shareholding on market performance (measured by Tobin Q). Panel data was gathered from twelve (12) banks listed on the Nigerian Stock Exchange from 2013 to 2017. The study used fixed and random regression analysis. The results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…The findings of this study support the conclusions of Satriyo and Harymawan [44]; and Tahir et.al., [47], which show a negative and significant link between Female CEOs and firm value, whereas the findings of Martin-ugedo, et al, [27]; and Dwlharti and Adhariani [10] in Spain and Indonesia show a positive and significant link between Female CEOs and firm performance. In Kenya, Gicheha and Muturi [13] found a negative and insignificant link between audit committee gender diversity and financial reports, supporting the findings of this study, whereas Mgbame, et al, [28]; and Omotoye, et al, [32] found a significant and positive link between audit committee gender diversity and market performance, contradicting the findings of this study.…”
Section: Gender Diversity and Earnings Per Share Of Listed Deposit Mo...contrasting
confidence: 56%
See 1 more Smart Citation
“…The findings of this study support the conclusions of Satriyo and Harymawan [44]; and Tahir et.al., [47], which show a negative and significant link between Female CEOs and firm value, whereas the findings of Martin-ugedo, et al, [27]; and Dwlharti and Adhariani [10] in Spain and Indonesia show a positive and significant link between Female CEOs and firm performance. In Kenya, Gicheha and Muturi [13] found a negative and insignificant link between audit committee gender diversity and financial reports, supporting the findings of this study, whereas Mgbame, et al, [28]; and Omotoye, et al, [32] found a significant and positive link between audit committee gender diversity and market performance, contradicting the findings of this study.…”
Section: Gender Diversity and Earnings Per Share Of Listed Deposit Mo...contrasting
confidence: 56%
“…Huang, Yan, Fornaro, and Elshahat [16] investigated market reactions to the gender of audit committee directors in their study Market reactions to the gender of audit committee directors: The selection of a female audit committee member has a robust favourable link with returns in US-traded overseas corporations. In the study on Audit committee qualities, board attributes, and market performance, Omotoye, Adeyemo, Omotoye, Okeme, and Leigh [32] found a significant positive association between audit committee gender diversity and market performance. Carter, D'Souza, Simkins, and Simpson [6] found no significant relationship between gender diversity in board committees and financial performance in their study The Gender and Ethnic Diversity of US Boards and Board Committees and Firm Financial Performance with a sample of US significant corporations.…”
Section: Female Board Audit Committeementioning
confidence: 97%
“…While it has been established in the literature that ACs are effective tools for corporate governance, they also serve to identify and remedy weaknesses in internal control, enhance the effectiveness of the board of directors' oversight, and coordinate the work of internal and external auditors (Bédard et al, 2004). However, in the Nigerian context, little research has examined the connection between specific AC attributes and firm performance (Omotoye et al, 2021;Orjinta & Evelyn, 2018;Osemene & Fakile, 2018). This necessitates more research to determine the influence of AC attributes on firm performance in Nigeria.…”
Section: Introductionmentioning
confidence: 99%